Perianesthesia nursing care a bedside guide for safe recovery - Stannard, Daphne; Krenzischek, Dina A. (Jones & Bartlett Learning, 2012)
A Bedside Guide to Safe Recovery is a key reference for clinicians practicing in preoperative areas, phase I and phase II PACU nursing areas, and nurses working in critical care, OB, and other specialty recovery units. Ideal for perianesthesia nursing orientation and perioperative cross-training programs, this text is beneficial for all those caring for pre-and-post-anesthesia patients. Additionally, it is a valuable tool for nursing students specializing in critical care and perianesthesia nurses preparing to sit for the Certified Post Anesthesia Nursing (CPAN) and Certified Ambulatory Perianesthesia Nurse (CAPA) certification examinations. Divided into three sections that cover the lifespan, Perianesthesia Nursing Care: A Bedside Guide to Safe Recovery is specifically designed to be functional for the clinician and grounding for the student nurse. The first section focuses on core concepts applicable to all perianesthesia patients and families, while the second is population specific, and the third concentrates on particular surgeries and procedures that follow body systems.